Pitting Corrosion of Ni3(Si,Ti)+4Al Intermetallic Compound at Various Chloride Concentrations - Gadang Priyotomo; Pius Sebleku; Yasuyuki Kaneno (Chemical Engineering Diponegoro University, 2014)
The pitting corrosion of Ni3(Si,Ti) with 4 at% Al consisting of two regions of a Ni3(Si,Ti) single-phase of L12 structure and two phases of L12 and fcc Niss was investigated as function of chloride concentrations by using electrochemical method, scanning electron microscope and energy dispersive X-Ray spectroscopy in neutral sodium chloride solutions at 293 K. In addition, the pitting corrosion of Ni3(Si,Ti) and type C276 alloy were also studied under the same experimental condition for comparison. The pitting potential obtained for the Ni3(Si,Ti) with 4 at%Al decreased with increasing chloride concentration. The specific pitting potential and pitting potential of Ni3(Si,Ti) with 4at%, Ni3(Si,Ti) and C276 were the lowest, the moderate and the highest, respectively, which means that the pitting corrosion resistance of Ni3(Si,Ti) was higher than Ni3(Si,Ti) with 4at% Al, but lower than that of C276. A critical chloride concentration of Ni3(Si,Ti) with 4at% Al was found to be lower than that of Ni3(Si,Ti). The Pitting corrosion of Ni3(Si,Ti) with 4at% Al occurred in the two phase mixture (L12 + Niss).